Association Between Sulfur Dioxide and Daily Inpatient Visits With Respiratory Diseases in Ganzhou, China: A Time Series Study Based on Hospital Data - Zhou, Xingye; Gao, Yanfang; Wang, Dongming; Chen, Weihong; Zhang, Xiaokang (Frontiers in Public Health, 2022)
Background Sulfur dioxide (SO2) has been reported to be related to the mortality of respiratory diseases, but the relationship between SO2 and hospital inpatient visits with respiratory diseases and the potential impact of different seasons on this relationship is still unclear. Methods The daily average concentrations of air pollutants, including SO2 and meteorological data in Ganzhou, China, from 2017 to 2019 were collected. The data on daily hospitalization for respiratory diseases from the biggest hospital in the city were extracted. The generalized additive models (GAM) and the distributed lag non-linear model (DLNM) were employed to evaluate the association between ambient SO2 and daily inpatient visits for respiratory diseases. Stratified analyses by gender, age, and season were performed to find their potential effects on this association. Results There is a positive exposure-response relationship between SO2 concentration and relative risk of respiratory inpatient visits. Every 10 μg/m3 increase in SO2 was related to a 3.2% (95% CI: 0.6–6.7%) exaltation in daily respiratory inpatient visits at lag3. In addition, SO2 had a stronger association with respiratory inpatient visits in women, older adults (≥65 years), and warmer season (May-Oct) subgroups. The relationship between SO2 and inpatient visits for respiratory diseases was robust after adjusting for other air pollutants, including PM10, NO2, O3, and CO. Conclusion This time-series study showed that there is a positive association between short-term SO2 exposure and daily respiratory inpatient visits. These results are important for local administrators to formulate environmental public health policies.